Queering Bardem: political and sexual repression in "Calle Mayor" - Pedrós-Gascón, Antonio Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This text analyzes Juan Antonio Bardem’s Calle Mayor from a queer point-of-view that centers on the relationship between Federico and Juan, instead of that existing between Isabel and Juan, that is traditional in the analyses of the work. Through the contextualization of this relationship within the setting of early-Francoism’s homosocial structure —the military camaraderie—, this essay proposes reading the work as a polyphonic entity that aims to coalesce different subjugated groups —women, homosexuals, communists and other political identities— , with the goal of consolidating a political consciousness against the regime.